Mechanically Tunable Bioink for 3D Bioprinting of Human Cells. Issue 20 (21st July 2017) - Forget, Aurelien; Blaeser, Andreas; Miessmer, Florian; Köpf, Marius; Campos, Daniela F. Duarte; Voelcker, Nicolas H.; Blencowe, Anton; Fischer, Horst; Shastri, V. Prasad
Abstract: This study introduces a thermogelling bioink based on carboxylated agarose (CA) for bioprinting of mechanically defined microenvironments mimicking natural tissues. In CA system, by adjusting the degree of carboxylation, the elastic modulus of printed gels can be tuned over several orders of magnitudes (5–230 Pa) while ensuring almost no change to the shear viscosity (10–17 mPa) of the bioink solution; thus enabling the fabrication of 3D structures made of different mechanical domains under identical printing parameters and low nozzle shear stress. Human mesenchymal stem cells printed using CA as a bioink show significantly higher survival (95%) in comparison to when printed using native agarose (62%), a commonly used thermogelling hydrogel for 3D‐bioprinting applications. This work paves the way toward the printing of complex tissue‐like structures composed of a range of mechanically discrete microdomains that could potentially reproduce natural mechanical aspects of functional tissues. Abstract : Carboxylated agarose hydrogels with mechanical property independent of the bioink solution viscosity allow the high‐viability 3D bioprinting of human mesenchymal stem cells. Furthermore, addition of collagen to the carboxylated agarose induces the proliferation of the human mesenchymal stem cells used in this study.